A Constraint-Based Approach of Vowel Epenthesis in Greek Child Speech - Poulidakis, Anastasios (e-Journal of Linguistics; Vol 18 No 2 (2024): ejl-JulyDO - 10.24843/e-jl.2024.v18.i02.p02, 2024)
This study investigates vowel epenthesis in Greek and aims to answer how this process facilitates language acquisition. More specifically, properties of vowel epenthesis are examined, such as the position and quality of the epenthetic vowel as well as whether it is affected by the stress system of the ambient language. Our findings are based on spontaneous speech collected from three Greek-speaking children aged 1;6.26 - 2;10.9 years old. An inserted vowel is observed at the end of monosyllabic and disyllabic loanwords so as to license a consonant that is not permitted in coda position by resyllabifying it to onset position in the new syllable. It additionally creates trochaic rhythm, which is the default stress pattern in Greek. This is especially shown from disyllabic loanwords and non-loanwords with iambic stress, which changes into trochaic with the addition of the new syllable. Further, only [+anterior] vowels are inserted due to them being always adjacent to a [CORONAL] consonant with which they share the same distinctive feature of place, namely, [+anterior]. The children’s data are analyzed according to Optimality Theory (Prince & Smolensky, 1993), in which the ranking of specific constraints can explain and interpret the properties of epenthesis.